N04 Interventions for managing fatigue in inflammatory bowel disease: A Cochrane systematic review. (25th January 2019) - Farrell, D; Savage, E; Norton, C; Jelsness-Jørgensen, L-P; Czuber-Dochan, W; Artom, M
Abstract: Background: Fatigue is a common, debilitating and burdensome symptom experienced by individuals with inflammatory bowel disease (IBD). The subjective, complex nature of fatigue can often hamper its' management, and the effectiveness of treatments for fatigue in IBD remains unknown. The aim of this Cochrane review is to assess the efficacy and safety of pharmacological and non-pharmacological interventions for managing fatigue in IBD. Methods: A systematic search was undertaken. Data were extracted and study quality was independently assessed by two authors. Standard Cochrane methodological procedures were used. Results: Fourteen randomised controlled trials were included (3741 participants; all adults; 6 in Crohn's disease (CD); 2 in ulcerative colitis (UC); 6 in both CD and UC). The interventions varied widely and included nine pharmacological trials, four non-pharmacological trials, and one multi-modular trial. Only four trials were designed specifically as interventions for managing fatigue. None of the included studies were free from risk of bias. Only one meta-analysis was possible, due to the diversity and limited number of studies for each intervention. We found some evidence suggesting possible improvements in fatigue for adalimumab 40 mg administered every other week and adalimumab maintenance therapy (only for those known to respond to adalimumab induction therapy), ferric maltol, electroacupuncture, self-directed stress management, solution focussed therapy and physical activity advice. We found no clear improvements in fatigue for adalimumab 40 mg administered weekly, Agaricus blazei Murill-based mushroom extract, guided stress management or omega-3. There was also no significant difference in fatigue scores between cognitive behavioural therapy with therapist support, compared with information leaflet only group, however this was a feasibility trial and a trend was observed. Reporting in some of the trials was insufficient to assess the efficacy and safety of some therapies, including vitamin D3 supplementation, ferumoxytol, vedolizumab, and tight control customised management. Conclusions: It is difficult to draw firm conclusions about the effectiveness of interventions to improve fatigue for individuals with IBD, as there is insufficient quantity and quality of evidence available. Further randomised controlled trials are needed to assess the efficacy of therapies specifically designed for fatigue management.